Molecular Detection and Multidrug Resistance of Shigella spp. Isolated from Wild Waterfowl and Migratory Birds in Bangladesh - Jarna Karmoker; Md. Saiful Islam; Md. Liton Rana; Md. Ashek Ullah; Fahim Haque Neloy; Nahian Muniath Oishy; Pritom Kumar Pramanik; Mahbubul Pratik Siddique; Sukumar Saha; Md. Tanvir Rahman (Veterinary Medicine International)
Birds, especially wild waterfowl and migratory birds have the potential to carry antibiotic-resistant bacteria, but their role in the dissemination of these resistant pathogens is still neglected in Bangladesh. To the best of our knowledge, this study was carried out for the first time in Bangladesh to isolate and determine the occurrence of multidrug-resistant (MDR) Shigella spp. from fecal materials of wild waterfowl and migratory birds. A total of 80 fecal materials from wild waterfowl (n = 50) and migratory birds (n = 30) were screened to detect MDR Shigella isolates. Shigella spp. were isolated and identified by culturing, staining, and biochemical tests followed by polymerase chain reaction (PCR). A disk diffusion assay was employed to investigate antibiotic phenotypes, while the resistance genes were detected by PCR. Among the 80 samples, 15 (18.75%) were found positive for Shigella spp. by PCR, among which the occurrence rate of Shigella spp. was higher in migratory birds (20%, 6/30) than in wild waterfowl (18%, 9/50). By the disk diffusion test, 86.67% (13/15) of Shigella spp. isolates were found to be MDR in nature, including 93.33% of isolates resistant to imipenem. Moreover, frequent and moderate resistance was also observed against tetracycline (86.67%), azithromycin (80%), ampicillin (66.67%), ciprofloxacin and cotrimoxazole (40%), meropenem (26.67%), and streptomycin (13.33%). The bivariate analysis revealed a positive correlation between the resistance profiles of ciprofloxacin and cotrimoxazole, imipenem and tetracycline, tetracycline and ampicillin, and imipenem and azithromycin. Furthermore, the isolates had a multiple antibiotic resistance index of up to 0.47. Antibiotic resistance genes tetA and SHV were found in 69.23% and 50% of relevant antibiotic-resistant Shigella spp. isolates, respectively. The present study suggests that wild waterfowl and migratory birds are reservoirs of MDR Shigella spp., which may have detrimental impacts on One Health components. We suggest keeping these birds under an AMR monitoring program to avoid the possibility of AMR contamination of the environment and its consequences in all health settings.